Incidence and prognostic impact of other cancers in a population of long-term survivors of chronic lymphocytic leukemia. (23rd February 2016) - Falchi, L.; Vitale, C.; Keating, M. J.; Lerner, S.; Wang, X.; Elhor Gbito, K. Y.; Strom, S.; Wierda, W. G.; Ferrajoli, A.
Abstract : This unique analysis selectively focused on very long-term survivors of chronic lymphocytic leukemia (CLL) shows that these patients, particularly males and individuals <60 years, are at higher risk for other cancers (OCs). The study also shows that CLL therapy is not an independent risk factor for OC in this population. Abstract: Background: Information on the impact of other cancers (OCs) in long-term survivors (LTSs) of chronic lymphocytic leukemia (CLL) is limited. Patients and methods: Patients with CLL who survived >10 years were defined as LTSs of CLL. We calculated standardized incidence ratios (SIRs) to compare the incidence of OC in LTS of CLL versus the general population. A multivariable model was used to identify independent predictors of OC. Overall survival was analyzed as a function of the presence of OC. Results: Among 797 LTSs of CLL, the cumulative frequency of OC was 36%, similar between 570 patients (72%) who required treatment for CLL (TRT) and 227 (28%) who remained untreated (UT). The most common OC in both groups was non-melanoma skin cancer, followed by prostate cancer, breast cancer, melanoma, lung cancer, and leukemia in TRT patients, and by prostate cancer, breast cancer, melanoma, lung cancer, and gastrointestinal tumors in the UT group. The SIR for all OC was 1.2 ( P = 0.034). It was higher in males (SIR 1.31; P = 0.013) and patients <60 years (SIR 1.27; P = 0.027). A higher SIR was shown for secondary leukemia, melanoma, and head-and-neck cancers, whereas a lower SIR was found for gastrointestinal and bladder cancers. Independent predictors of OC development were advanced age, male gender, and lower platelets. The survival of patients with OC was 16.2 months and that of patients without OC 22.9 years. Conclusions: LTSs of CLL have an increased incidence of OC compared with the general population. CLL therapy is not a risk factor for OC in LTSs of CLL. The presence of an OC in these patients may be associated with shorter survival.